Mapping of Bruise of Oil Palm Fresh Fruit Bunch during Loading and Transportation from Field to Mill - Krisdiarto, Andreas Wahyu (Makara Journal of Technology, 2018)
Fresh fruit bunches (FFBs) are used as raw materials for palm oil, and their transport from a field is a critical step to maintain their quality. Fruit integrity should be maintained so the mill can efficiently obtain palm oil with less than 5% free fatty acid content. Physical treatments for FFBs during loading to truck bins and transport may cause physical injuries. This research aimed to map fruit bruises. The map can be used as a basis in managing transport of FFBs. Physical injuries were assessed by bruise index (BI), which was calculated by measuring the bruise area and weight of the fruit. The experiment was conducted in a completely randomized design (CRD) with five replications. The treatments included truck type (wood bin or steel bin), truck age (more and less than 5 years), and FFB position in the truck bin (bottom, middle, top layer, front, center, or rear). Data were described by graphical method and analyzed statistically with one-way ANOVA. Results indicated loosen fruits and increased bruising of matured fruits loaded to the truck bin. BI (1.97–2.07) was not significantly different among FFBs placed in different positions in the truck bin. Nevertheless, FFB at the middle position showed higher degree of bruising than FFBs at the other positions. Fruit bruise was more prevalent when FFBs were transported by an old truck (>5years) rather than by a young truck, with BI values of 2.01 and 1.82, respectively.